2021
DOI: 10.3390/molecules26206203
|View full text |Cite
|
Sign up to set email alerts
|

Studies towards the Design and Synthesis of Novel 1,5-Diaryl-1H-imidazole-4-carboxylic Acids and 1,5-Diaryl-1H-imidazole-4-carbohydrazides as Host LEDGF/p75 and HIV-1 Integrase Interaction Inhibitors

Abstract: Two targeted sets of novel 1,5-diaryl-1H-imidazole-4-carboxylic acids 10 and carbohydrazides 11 were designed and synthesized from their corresponding ester intermediates 17, which were prepared via cycloaddition of ethyl isocyanoacetate 16 and diarylimidoyl chlorides 15. Evaluation of these new target scaffolds in the AlphaScreenTM HIV-1 IN-LEDGF/p75 inhibition assay identified seventeen compounds exceeding the pre-defined 50% inhibitory threshold at 100 µM concentration. Further evaluation of these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Imidazole-containing molecules demonstrate a wide variety of antiviral activities. Only recently papers on antiviral activity of imidazole derivatives against Hepatitis C virus 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , Hepatitis B virus [38] , influenza A virus 39 , 40 , dengue virus 41 , 42 , Chikungunya virus [43] , rhabdoviridae 44 , 45 , 46 , 47 , 48 , herpesviridae [49] , Human Cytomegalovirus [50] , HIV-1 [51] and coronaviruses [52] have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole-containing molecules demonstrate a wide variety of antiviral activities. Only recently papers on antiviral activity of imidazole derivatives against Hepatitis C virus 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , Hepatitis B virus [38] , influenza A virus 39 , 40 , dengue virus 41 , 42 , Chikungunya virus [43] , rhabdoviridae 44 , 45 , 46 , 47 , 48 , herpesviridae [49] , Human Cytomegalovirus [50] , HIV-1 [51] and coronaviruses [52] have been published.…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of some alkaloidal compounds extracted from fungus‐treated leaves are summarized in Table 2. Among the identified compounds, there are various compounds that exhibited wide biological activities such as 2,5‐Difluoro‐1‐(tri‐acetyl ribo‐furanosyl) imidazole‐4‐carboxylic acid, ethyl ester (Narasimhan et al, 2011; Rashamuse et al, 2021), Estra‐1,3,5(10)‐trien‐17.beta.‐ol (Al‐Gara et al, 2019), Cholestan‐6‐one, 3‐(acetyloxy)‐, (3.beta.,5.alpha.) (Jegadeeswari et al, 2012), 3‐(3‐Fluoroanilino)‐1‐(3‐nitrophenyl)‐1‐propanone (Eswaraiah et al, 2020), and Quinoline, 2‐(4‐methylphenyl) (Matada et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The biological activities of some alkaloidal compounds extracted from fungus-treated leaves are summarized in Table 2. Among the identified compounds, there are various compounds that exhibited wide biological activities such as 2,5-Difluoro-1-(tri-acetyl ribo-furanosyl) imidazole-4-carboxylic acid, ethyl ester (Narasimhan et al, 2011;Rashamuse et al, 2021), Beauveria sp. AUMC 15401 colonization into tomatoes could stimulate the secretion of other important biologically active metabolites that showed a promising cytotoxic effect.…”
Section: Gc-ms Analysis Of the Alkaloidal Extractmentioning
confidence: 99%
“…Alvarez Ibarra et al [48] have further reported the synthesis of 2-etylthio-4-carbethoxy-5-alkyl/arylaminothiazoles by treatment of EMIC in the presence of potassium t-butoxide with isothiocyanate in THF: Takeda et al [49] have devised an ingenious method of synthesizing 2-amino-5-arylthiazole-4-carboxylates by the following:…”
Section: Synthesis Of Thiazole and Its Derivativesmentioning
confidence: 99%